A framework for effective food supply chain safety controls/ Siti Norida Wahab ... [et al.] - Wahab, Siti Norida; Rajendran, Salini Devi; Ling, Eric Kaiyue; Mukherjee, Aroop (Universiti Teknologi MARA Selangor, 2022)
Food safety assurance is becoming a prevalent concern due to several food scandals that have eroded customer trust and confidence. Despite the importance of food safety, little is known about the current state of food supply chain safety controls (FSCSC). Therefore, this study aims to identify and establish a conceptual model for FSCSC. To gain a preliminary grasp of the impetus behind the FSCSC, this study applied a comprehensive literature review to fully integrate the various elements that drive FSCSC. Relevant literature on food safety, food quality, and food safety control measures is being scrutinized. Regulation and legislation, traceability and trackability, technology, and human capital are recognized as important aspects to enhance FSCSC. All four main aspects provide a communication network that is capable of aiding food controllers to verify, identify, and isolate potential sources of contamination. Insights from this study could offer a better understanding of FSCSC and serve as a platform for future empirical research. This study proposed an alternative strategy to transform the current FSCSC. Hence, future studies could incorporate inquiry, indepth evaluation, and panel interviews to gain a more comprehensive understanding of the general awareness of FSCSC processes.